Creativity and Rationale Enhancing Human Experience by Design - Carroll, John M. (Human-Computer Interaction Series, 2013)
Creativity and rationale comprise an essential tension in design. They are two sides of the coin; contrary, complementary, but perhaps also interdependent. Designs always serve purposes. They always have an internal logic. They can be queried, explained, and evaluated. These characteristics are what design rationale is about. But at the same time designs always provoke experiences and insights. They open up possibilities, raise questions, and engage human sense making. Design is always about creativity. Creativity and Rationale: Enhancing Human Experience by Design comprises 19 complementary chapters by leading experts in the areas of human-computer interaction design, sociotechnical systems design, requirements engineering, information systems, and artificial intelligence. Researchers, research students and practitioners in human-computer interaction and software design will find this state of the art volume invaluable.